Emergence of Carbapenem-Resistant Gram-Negative Isolates in Hospital Settings in Djibouti - Ayan Ali Ragueh; Mohamed Houmed Aboubaker; Sitani Idriss Mohamed; Jean-Marc Rolain; Seydina M. Diene (MDPI AG, 2023)
Introduction: The antimicrobial resistance (AMR) of bacteria is increasing rapidly against all classes of antibiotics, with the increasing detection of carbapenem-resistant isolates. However, while growing prevalence has been reported around the world, data on the prevalence of carbapenem resistance in developing countries are fairly limited. In this study, we investigated and determined the resistance rate to carbapenems among multidrug-resistant Gram-negative bacteria (MDR-GNB) isolated in Djibouti and characterized their resistance mechanisms. Results: Of the 256 isolates, 235 (91.8%) were identified as Gram-negative bacteria (GNB). Of these GNBs, 225 (95.7%) isolates exhibited a multidrug resistance phenotype, and 20 (8.5%) isolates were resistant to carbapenems, including 13 Escherichia coli, 4 Acinetobacter baumannii, 2 Klebsiella pneumoniae and 1 Proteus mirabilis. The most predominant GNB in this hospital setting were E. coli and K. pneumoniae species. Carbapenemase genes such as blaOXA-48 and blaNDM-5 were identified, respectively, in six and four E. coli isolates, whereas the carbapenemase blaNDM-1 was identified in three E. coli, two K. pneumoniae, one P. mirabilis and one A. baumannii. Moreover, three A. baumannii isolates co-hosted blaOXA-23 and blaNDM-1. Materials and Methods: A total of 256 clinical strains collected between 2019 and 2020 were identified using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). Antibiotic susceptibility testing was performed using disk diffusion and E-test methods. Real-time polymerase chain reaction (RT-PCR), standard PCR and sequencing were used to investigate genes encoding for extended-spectrum-β-lactamases, carbapenemases and colistin resistance genes. Conclusions: We report, for the first time, the presence of MDR-GNB clinical isolates and the emergence of carbapenem-resistant isolates in Djibouti. In addition to performing antimicrobial susceptibility testing, we recommend phenotypic and molecular screening to track the spread of carbapenemase genes among clinical GNB isolates.